Endothelial AGGF1 promotes retinal angiogenesis by coordinating TNFSF12/FN14 signalling - Ying Cheng; Man Zhang; Chenguang Li; Long Su; Lingli Fu; Shi Wu; Chaofei Xu; Bei Sun; Liming Chen (Nature Communications)
Abstract Abnormal angiogenesis is a key process associated with ischaemic retinopathies such as diabetic retinopathy, for which the underlying pathological mechanisms are still poorly understood. Here, we confirm that angiogenic factor 1 with a G patch and FHA domain (AGGF1) is elevated in the diabetics and induces retinal angiogenesis. Mechanistic investigations demonstrate that HIF-1α directly regulates AGGF1 expression. AGGF1 upregulates the expression of cell cycle proteins by increasing the binding of tumour necrosis factor ligand superfamily member 12 (TNFSF12) to fibroblast -growth -factor-inducible 14 (FN14, TNFRSF12A). Furthermore, targeting AGGF1 attenuates pathological neovascularisation in ischaemic retinopathy. Additionally, we discover that sodium-glucose cotransporter 2 inhibitors (SGLT2i) could inhibit the AGGF1 signalling pathway early to achieve therapeutic effects. Overall, we elucidate the mechanism underlying pathological retinal angiogenesis involved in endothelial AGGF1-dependent events and highlight a therapy for the effective treatment of ischaemic retinopathy.